The Civil Liability of Heirs in Lawsuits for the Recovery of State Losses Due to Corruption Committed by a Deceased Perpetrator Under Indonesian Positive Law - Amelia Oktaviani; Nuzul Rahamayani (SEAN Institute, 2026)
Corruption is an extraordinary crime that inflicts severe financial losses on the state. When a corruptor dies before or during the legal process, criminal prosecution is legally dropped, yet the state's financial losses persist, prompting civil lawsuits against the heirs to recover the corrupted assets. This research aims to analyze the form of civil liability of heirs and the legal protections afforded to them in lawsuits for state loss recovery under Indonesian positive law. This study employs a normative juridical approach of a descriptive-analytical nature, utilizing primary statutory materials and a case study of the Nabire District Court Decision No. 47/Pdt.G/2023/PN Nab, which are analyzed qualitatively. The results indicate that the heirs' civil liability is purely restitutive and strictly limited to the value of the inherited estate (boedel waris), meaning they do not bear personal responsibility for the deceased's crimes. Furthermore, legal protection is robustly guaranteed through the limitation of liability up to the inheritance value and the fundamental right to reject the inheritance entirely. In conclusion, Indonesian civil law effectively prevents the covert criminalization of heirs while maintaining the state's right to asset recovery. These findings are crucial for providing legal certainty to law enforcement, particularly State Attorneys, in executing proportional and just asset recovery strategies.